Memahami Karakteristik Generasi untuk Pengembangan Pelayanan Berbasis Generasi di Gereja Masehi Injili di Timor - Merensiana Hale (Asosiasi Teolog Indonesia, 2023)
The church in its ministry is ever sensitive to respond to the needs of the congregation according to the times. Congregations comprised of several generations often become mired in congregational divisions, stemming from generational gap issues that then foment intergenerational conflicts. To respond to this problem, the church must equip itself with insights into generational characteristics so as to improve generation-based ministries. Therefore, this paper promotes the convergence of generational theory and church ministry, to enrich the church by means of an understanding of generations according to their characteristics. Toward these aims, a methodological literature review yields that generational theory presents a major contribution for the church that seeks to maximize its congregational ministry towards all who belong to God. For Gereja Masehi Injili di Timor, (Evangelical Christian Church in Timor), having a good understanding of generational theory and how it contributes to ministry is useful for developing and implementing strategies involving intergenerational Christian education.